Editorial Board and Guideline for the Authors - SOSIOHUMANIKA, Editor Journal (SOSIOHUMANIKA, 2016)
SOSIOHUMANIKA will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment, and analysis on the key issues surrounding the humanities and social sciences education and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: May 20, 2016.Sincerely yours,Prof. Dr. H.R. Asep KadarohmanEditor-in-Chief of the SOSIOHUMANIKA JournalÂ